2010
DOI: 10.1158/0008-5472.sabcs10-p3-02-08
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P3-02-08: Detection of Circulating Tumor Cells Prior to Autologous Stem Cell Transplantation Is Predictive of Shorter Progression Free Survival in Metastatic Breast Cancer

Abstract: Background: High dose chemotherapy (HDCT) in patients with metastatic breast cancer (MBC) followed by autologous hematopoietic stem cell transplantation (ASCT) offers high complete response rates compared to standard therapy. However, the bone marrow (BM) is a reservoir for disseminated tumor cells (DTC) and the inadvertent recruitment from BM of DTC, cancer stem cells (CSC), and non-leukocytes undergoing epithelial mesenchymal transition (EMT) during the CD34+ hematopoietic progenitor cell (HPC) mobilization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The presence of CTC levels predicted poor progression -free survival and OS, independent of the tumor markers, however; elevated levels of CA 15-3, CEA and LDH were prognostic for PFS, but only LDH remained prognostic for OS [16]. Gao et al [17]showed CTCs in MBC prior to SCT were predictive of shorter PFS.…”
Section: Introductionmentioning
confidence: 98%
“…The presence of CTC levels predicted poor progression -free survival and OS, independent of the tumor markers, however; elevated levels of CA 15-3, CEA and LDH were prognostic for PFS, but only LDH remained prognostic for OS [16]. Gao et al [17]showed CTCs in MBC prior to SCT were predictive of shorter PFS.…”
Section: Introductionmentioning
confidence: 98%